Association Analysis of IL10, TNF-α, and IL23R-IL12RB2 SNPs with Behçet’s Disease Risk in Western Algeria - Khaib Dit Naib, Ouahiba; Aribi, Mourad; Idder, Aicha; Chiali, Amel; Sairi, Hakim; Touitou, Isabelle; Lefranc, Gérard; Barat-Houari, Mouna (Frontiers in Immunology, 2013)
Objective: We have conducted the first study of the association of interleukin (IL)-10, tumor necrosis factor alpha (TNF-α) and IL23R-IL12RB2 regionSNPswith Behçet's disease (BD) in Western Algeria. Methods: A total of 51 BD patients and 96 unrelated controls from West region of Algeria were genotyped by direct sequencing for 11 SNPs including 2 SNPsfrom the IL10 promoter [c.-819T>C (rs1800871), c.-592A>C (rs1800872)], 6 SNPs from the TNF-α promoter [c.-1211T>C (rs1799964), c.-1043C>A (rs1800630), c.-1037C>T (rs1799724), c.-556G>A (rs1800750), c.-488G>A (rs1800629) and c.-418G>A (rs361525)], and 3 SNPs from the IL23R-IL12RB2 region [g.67747415A>C (rs12119179), g.67740092G>A (rs11209032) and g.67760140T>C (rs924080)]. Results: The minor alleles c.-819T and c.-592A were significantly associated with BD (OR= 2.18; 95% CI 1.28-3.73, p = 0.003); whereas, there was weaker association between TNF-αpromoter SNPs or IL23R-IL12RB2 region and disease risk. Conclusion: Unlike the TNF-αand the IL23R-IL12RB2 region SNPs, the two IL10 SNPs were strongly associated with BD. The -819T, and -592A alleles and the -819TT, -819CT, and -592AA and -592CA genotypes seem to be highly involved in the risk of developing of BD in the population of Western Algeria.